Pre-labour fetal cerebro-umbilical ratio is predictive of intra-partum fetal distress. (18th April 2012) - Prior, T; Mullins, E; Bennett, P; Kumar, S
Abstract : The majority of infants that become distressed in labour have had a normal antenatal course. Currently there is no way of identifying infants at high risk of intra-partum problems. The fetal cerebro-umbilical ratio has been suggested as a marker of placental function and has been shown to be significantly lower in growth restricted infants. We investigated if measurement of the fetal cerebro-umbilical ratio prior to labour could identify babies at high risk of intra-partum fetal distress. In this prospective study, 250 women with uncomplicated term pregnancies underwent a pre-labour ultrasound assessment. The fetal cerebro-umbilical ratio (Middle Cerebral artery pulsatility index/Umbilical artery pulsatility index) was recorded. Labour was then managed as routine. Information obtained from the ultrasound scan was not made available to staff managing the labour. Intra-partum and neonatal outcome details were then recorded. Infants born by emergency caesarean section for fetal distress had significantly lower mean cerebro-umbilical ratios (1.47), compared to infants delivered by spontaneous vaginal delivery (1.80) (p = <0.001), or by instrumental delivery for a prolonged 2 nd stage (1.94) (p = <0.001). Thirty six percent of infants with a cerebro-umbilical ratio <10 th centile required delivery by emergency caesarean section due to fetal distress, compared with 0% of infants with a cerebro-umbilical ratio >90 th centile. This data suggests that measurement of the cerebro-umbilical ratio in normal term pregnancies can identify a cohort of infants at increased risk of intra-partum fetal compromise. Pre-labour measurement of the cerebro-umbilical ratio may therefore be helpful in the intra-partum management of selected cases.